Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/17470218.2016.1247899
|View full text |Cite
|
Sign up to set email alerts
|

Own-age biases in adults’ and children’s joint attention: Biased face prioritization, but not gaze following!

Abstract: Previous studies have reported own-age biases in younger and older adults in gaze following. We investigated own-age biases in social attentional processes between adults and children by focusing on two aspects of the joint attention process; the extent to which people attend towards an individual's face, and the extent to which they fixate objects that are looked at by this person (i.e., gaze following). Participants viewed images that always contained a child and an adult who either looked towards each other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
3
3
0
Order By: Relevance
“…This supports previous evidence that gaze cues orient attention in a very fast and automatic manner that is difficult to inhibit (Driver et al, 1999;Freebody & Kuhn, 2016;Frischen & Tipper, 2004). Although previous research has found that cueing can be mediated by factors such as social status , dominance (Jones et al, 2010), familiarity (Deaner, Shepherd, & Platt, 2007), race (Dalmaso et al, 2015;Pavan et al, 2011) and trustworthiness (Petrican et al, 2013;Süßenbach & Schönbrodt, 2014), we found no evidence that participants spontaneously considered either of the latter features when processing gaze, suggesting that these mediating effects may rely on the context (e.g., perceived threat) in which participants find themselves experiencing gaze cues.…”
Section: Discussionsupporting
confidence: 91%
“…This supports previous evidence that gaze cues orient attention in a very fast and automatic manner that is difficult to inhibit (Driver et al, 1999;Freebody & Kuhn, 2016;Frischen & Tipper, 2004). Although previous research has found that cueing can be mediated by factors such as social status , dominance (Jones et al, 2010), familiarity (Deaner, Shepherd, & Platt, 2007), race (Dalmaso et al, 2015;Pavan et al, 2011) and trustworthiness (Petrican et al, 2013;Süßenbach & Schönbrodt, 2014), we found no evidence that participants spontaneously considered either of the latter features when processing gaze, suggesting that these mediating effects may rely on the context (e.g., perceived threat) in which participants find themselves experiencing gaze cues.…”
Section: Discussionsupporting
confidence: 91%
“…Our results illustrate that when participants freely viewed images (Experiment 1), the model's gaze/head orientation influenced where people look. In line with previous research (Fletcher-Watson et al, 2008;Freebody & Kuhn, 2016;Zwickel & Vo, 2010) participants were significantly faster and spent significantly more time fixating objects that were looked towards by the model. However, this effect was not observed when a barrier interrupted the model's line of sight.…”
Section: Discussionsupporting
confidence: 90%
“…Once the video appeared, all participants immediately fixated the magician's face, which coincides with a large body of research illustrating that faces are prioritized (Birmingham, Bischof, & Kingstone, 2008;Fletcher-Watson, Leekam, Benson, Frank, & Findlay, 2009;Yarbus, 1967). The time to fixate on the face provides valuable insights into the automatic nature of this social attentional orienting (Fletcher-Watson et al, 2009;Freebody & Kuhn, 2016;Kuhn, Kourkoulou, & Leekam, 2010;Zwickel & Vo, 2010). Our children were significantly faster to fixate on the face (M = 260 ms; SD = 53) than the adults (M = 319 ms; SD = 122), t(57) = 2.36, p = .022, which further supports the view that children's eye movements are more strongly driven by bottom-up processes.…”
Section: Discussionsupporting
confidence: 65%